A comparison of the poverty impact of transfers, taxes and market income across five OECD countries - Sami Bibi; Jean-Yves Duclos (Institute for the Study of Labor (IZA), 2008)
This paper compares the poverty reduction impact of income sources, taxes and transfers across five OECD countries. Since the estimation of that impact can depend on the order in which the various income sources are introduced into the analysis, it is done by using the Shapley value. Estimates of the poverty reduction impact are presented in a normalized and un-normalized fashion, in order to take into account the total as well as the per dollar impacts. The methodology is applied to data from the Luxembourg Income Study (LIS) database.
urn:nbn:de:101:1-20081127531
Keywords: D31; 330; Poverty reduction; transfers; taxes; Shapley value; OECD countries; Sozialtransfer; Steuer; Wirkungsanalyse; Armutspolitik; Funktionelle Einkommensverteilung; Shapley-Wert; Kanada; USA; Deutschland; Schweden